2019
DOI: 10.1128/iai.00081-19
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Parasite Persistence Drives Vasculitis and Myositis in Skeletal Muscle of Mice Chronically Infected with Trypanosoma cruzi

Abstract: In chronic Trypanosoma cruzi infection, the cause of Chagas disease, life-threatening inflammatory diseases develop over time in the heart, esophagus, and colon of some patients. C57BL/6 mice infected with the myotropic Colombiana strain of T. cruzi model many of the immunological and parasitological features of human infection but succumb to chronic paralyzing myositis and skeletal muscle vasculitis, not cardiomyopathy or gastrointestinal disease. Here we show that T cell depletion in the chronic phase of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…5c ). Some T. cruzi strains have been reported to be myotropic in mice, with pathological outcomes that include paralyzing myositis and skeletal muscle vasculitis ( 32 ). Myocyte infections could also provide the parasite with access to myoglobin, a source of heme or iron that may contribute to a nutritional environment that is favorable for replication.…”
Section: Discussionmentioning
confidence: 99%
“…5c ). Some T. cruzi strains have been reported to be myotropic in mice, with pathological outcomes that include paralyzing myositis and skeletal muscle vasculitis ( 32 ). Myocyte infections could also provide the parasite with access to myoglobin, a source of heme or iron that may contribute to a nutritional environment that is favorable for replication.…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompetent individuals, most parasitic infections are generally considered self-limited, indicating the development and the maintenance of protective immune mechanisms against invading parasites (Okhuysen, 2001; Meamar et al, 2006; Saporito et al, 2013; Lanocha-Arendarczyk et al, 2018). However, multiple studies have suggested that host immune responses elicited during parasitic infections can mediate immunopathology and are responsible for many of the symptoms commonly observed during parasitic diseases (Phillips and Fox, 1984; Pesce et al, 2006; Babaei et al, 2016; Ivanova et al, 2019; Weaver et al, 2019). These immunopathological changes may include parasite-induced morphological, functional, physiological, and structural alterations in parasitized tissues/cells, rendering infected individuals susceptible to organ dysfunction as well as the development of severe forms of clinical disease (Solaymani-Mohammadi and Singer, 2013; Taniguchi et al, 2015; Gorosito Serran et al, 2017; Ma'ayeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Protein p I -shifts due to PTMs revealed that the theoretical p I -value of the non-acetylated form of tropomyosin-beta is close to the p I -value of its experimentally acetylated counterpart, while additional acetylation of tropomyosin (LEKTIDDLEETLASAK + acetyl (K); acetyl (N-term)) does not significantly affect the p I -value [222]. Interestingly, a variety of contractile proteins are changed in chronic Chagas disease, an often fatal outcome of Trypanosoma cruzi infection, which is characterized by severe cardiomyopathy and chronic skeletal muscle myositis and vasculitis [223,224]. Protein changes were evaluated using 2DGE of specimens from end-stage chronic Chagas disease patients to gain insight into its pathophysiology [225].…”
Section: Top-down Proteomics Of Contractile Proteins From Skeletalmentioning
confidence: 99%